To solve this system of equations, we can substitute the value of x from the second equation into the first equation:
2(5y-1) + 6y = -18
10y - 2 + 6y = -18
16y - 2 = -18
16y = -16
y = -1
Now that we have the value of y, we can substitute it back into the second equation to find the value of x:
x = 5(-1) - 1
x = -5 - 1
x = -6
Therefore, the solution to the system of equations is (-6, -1). So the correct response is:
(-6, -1)
Solve the system of equations.
2x+6y=−18
x=5y−1(1 point)
Responses
(−7.25, −1.25)
left parenthesis negative 7.25 comma negative 1.25 right parenthesis
(−6, −1)
left parenthesis negative 6 comma negative 1 right parenthesis
(5.25, 1.25)
left parenthesis 5.25 comma 1.25 right parenthesis
(4, 1)
1 answer